Kewirausahaan dan Panggilan Kristen: Sebuah Pendekatan Interpretatif-Dialogis, Sosio-Historis dan Teologis - Suwarto Adi (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2020)
Is it possible to entrepreneurship as a Christian calling? This paper answers to this question by doing a combination of socio-historical and theological approaches. Historically, the ideas of entrepreneurship and its practices are undergoing a meaningful development. While from a theological perspective it delivered an ethical meaning if entrepreneurship located in the frame of a theology of creation and social action to build a common justice. This is all affiliates with mentality of God in the creation process of the world and Jesus’ criticism of a greedy attitude. Paul, furthermore, making entrepreneur-ship is as a constructive way of his service. Eventually, if locating entrepreneur-ship in Rahner’s framework in terms of intellectual, res, and opera, it could be a base of Christian calling to create community welfare and justice. Abstrak Apakah mungkin kewirausahaan menjadi panggilan Kristen? Tulisan ini menjawab pertanyaan tersebut dengan menggabungkan pendekatan sosio-historis dan teologis. Secara historis, gagasan dan praktik kewirausahaan mengalami perkembangan bermakna. Sedangkan, dari perspektif teologis, makna etis kewirausahaan akan lahir kalau diletakkan dalam kerangka penciptaan dan tindakan membangun keadilan Bersama. Hal itu bersesuaian dengan mentalitas Allah dalam proses penciptaan dan kritik Yesus terhadap ketamakan. Paulus, lebih jauh lagi menjadikan kewirausahaan sebagai jalan pelayanan yang konstruktif. Akhirnya, dengan meletakannya dalam kerangka intellectus, res dan opera-nya Karl Rahner, kewirausahaan bisa dijadikan dasar bagi panggilan Kristen untuk menciptakan kesejahteraan dan keadilan masyarakat